VV-exchange in direct Monte Carlo simulation of rarefied gas flows - Bondar, Ye.A.; Gimelshein, S.F.; Molchanova, A.N.; Ivanov, M.S. (Numerical Methods and Programming (Vychislitel’nye Metody i Programmirovanie), 2014)
A question of modeling of vibration-vibration (VV) exchange in calculation of rarefied gas flows by the direct simulation Monte Carlo method is considered. Two simple models for VV-exchange in collisions of simple harmonic oscillator molecules are proposed: a model with single-quantum transitions and an extension of the Larsen-Borgnakke model used widely for RT- and VT-exchange. Computation of vibrational relaxation is performed for homogeneous test conditions and for the conditions of an experiment on vibrational population evolution in nitrogen excited vibrationally by a laser. The numerical results obtained are in good agreement with experimental data.